Analysis of Student Errors in Completing Spotting of Round Numbers Based on Castolan Theory - Rahma Aulia Sari; Wulida Arina Najwa (LPPM Universitas Buana Perjungan Karawang, 2021)
Learning mathematics requires the ability to think logically and critically, not only learning to count. Therefore, teaching concepts is very important. Many students have incorrect, incomplete concepts and so on. As a result, mistakes occur when students do simple mathematics. This research was conducted with the aim of knowing the errors in the castor stage. The stages of castor are used including concept errors, procedure errors and technic errors. This research is a qualitative research. The research subjects were students of grade VI SDN Belitung Selatan 1 Banjarmasin. The procedure for selecting subjects used purposive sampling. The data techniques used were tests and interviews. The test is in the form of description questions. The data analysis technique used was data reduction, data presentation and data collection. Based on the research data, it can reveal that students made misconceptions, procedural errors and technical errors. Each student made these mistakes with different indicators.